Activation of GABAergic Neurons in the Rostromedial Tegmental Nucleus and Other Brainstem Regions Promotes Sedation and Facilitates Sevoflurane Anesthesia in Mice - Vlasov, Ksenia (Anesth Analg, 2021)
Many general anesthetics potentiate GABA(A) receptors but their neuroanatomic sites of action are less clear. GABAergic neurons in the rostromedial tegmental nucleus (RMTg) send inhibitory projections to multiple arousal-promoting nuclei, but the role of these neurons in modulating consciousness is unknown. In this study, designer receptors were targeted to RMTg GABAergic neurons of Vgat-ires-Cre mice. DREADDs expression was found in the RMTg and other brainstem regions. Activation of these neurons decreased movement and exploratory behavior, impaired motor coordination, induced EEG oscillations resembling NREM sleep without loss of righting, and reduced the dose requirement for sevoflurane-induced unconsciousness. These results suggest that GABAergic neurons in the RMTg and other brainstem regions promote sedation and facilitate sevoflurane-induced unconsciousness.